Reinforcement of poly-l-lactic acid electrospun membranes with strontium borosilicate bioactive glasses for bone tissue engineering. (15th October 2016) - Fernandes, João S.; Gentile, Piergiorgio; Martins, Margarida; Neves, Nuno M.; Miller, Cheryl; Crawford, Aileen; Pires, Ricardo A.; Hatton, Paul; Reis, Rui L.
Graphical abstract: Abstract: Herein, for the first time, we combined poly-l -lactic acid (PLLA) with a strontium borosilicate bioactive glass (BBG-Sr) using electrospinning to fabricate a composite bioactive PLLA membrane loaded with 10% (w/w) of BBG-Sr glass particles (PLLA-BBG-Sr). The composites were characterised by scanning electron microscopy (SEM) and microcomputer tomography (μ-CT), and the results showed that we successfully fabricated smooth and uniform fibres (1–3 μm in width) with a homogeneous distribution of BBG-Sr microparticles (<45 μm). Degradation studies (in phosphate buffered saline) demonstrated that the incorporation of BBG-Sr glass particles into the PLLA membranes increased their degradability and water uptake with a continuous release of cations. The addition of BBG-Sr glass particles enhanced the membrane's mechanical properties (69% higher Young modulus and 36% higher tensile strength). Furthermore, cellular in vitro evaluation using bone marrow-derived mesenchymal stem cells (BM-MSCs) demonstrated that PLLA-BBG-Sr membranes promoted the osteogenic differentiation of the cells as demonstrated by increased alkaline phosphatase activity and up-regulated osteogenic gene expression ( Alpl, Sp7 and Bglap ) in relation to PLLA alone. These results strongly suggest that the composite PLLA membranes reinforced with the BBG-Sr glass particles have potential as an effective biomaterial capable of promoting bone regeneration. Statement of Significance: PLLA membranes were reinforced with 10% (w/w) of strontium-bioactive borosilicate glass microparticles, and their capacity to induce the osteogenic differentiation of bone marrow mesenchymal stem cells (BM-MSCs) was evaluated. These membranes presented an increased: degradability, water uptake, Young modulus and tensile strength. We also demonstrated that these membranes are non-cytotoxic and promote the attachment of BM-MSCs. The addition of the glass microparticles into the PLLA membranes promoted the increase of ALP activity (under osteogenic conditions), as well as the BM-MSCs osteogenic differentiation as shown by the upregulation of Alpl, Sp7 and Bglap gene expression. Overall, we demonstrated that the reinforcement of PLLA with glass microparticles results in a biomaterial with the appropriate properties for the regeneration of bone tissue.